Haworth, Republic County - Hall, Rebecca (Kansas State University, The Chapman Center for Rural Studies, 2012)
The lost town of Haworth, located in Republic County, Kansas, was built and settled along an existing railway. Many of the inhabitants including the Haworth family were from the Midwest travelling west in search of better opportunities. This study provides a history of Haworth using maps, newspapers and photographs.
Rebecca Hall, “Haworth, Republic County,” Chapman Center Research Collections, accessed October 23, 2020, https://ccrsresearchcollections.omeka.net/items/show/108.
Keywords: Belleville; Burlington and Missouri Railroad; Chicago Iowa and Kansas Railroad; Republic County; Scandia; Mill Creek